Chapter Introduzione - Carocci, Sandro (Reti Medievali E-Book, 2023)
The introduction, after recalling the aims of the PRIN project from which this volume originates and describing the criteria used in the census of the lordships present in 14th-15th century Italy, illustrates the four main themes dealt with in the essays collected in the volume: the sources produced and collected by the lordships, the relations between lordship and external powers, the economy, and the societies subject to the lords. Finally, it asks whether, despite the many geographical differences, it is possible to discern a specificity of the Italian lordship with respect to that of other European regions.